Influence of the surface roughness of particleboards and their performance towards coating - Rolleri, A.; Roffael, E. (Maderas. Ciencia y Tecnología, 2025)
Las propiedades de la superficie y su efecto en la calidad de la adhesion fueron evaluadas en tableros pintados. Tableros de partículas sin recubrir encolados con resinas UF y TF hechos utilizando diferentes materias primas fueron acondicionados a clima 20°C and 65 % de humedad relativa fueron pintados con un aparejo nitrocelulósico mediante un proceso convencional. La interacción entre el aparejo y la superficie parece ser un importante factor que determina la fuerza de la adherencia. Abstract The effect of surface properties on the quality of the adhesion was evaluated for coated particleboards. Uncoated UF- and TF-bonded particleboards made using different raw materials were conditioned under 20°C and 65 % relative humidity and coated with a nitrocellulose lacquer primer by a conventional process. The interaction between the primer and surface seems to be a very important factor determining the strength of adherence.